2022
DOI: 10.1007/s11696-022-02299-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring bimetallic Au–Ag core shell nanoparticles reduced using leaf extract of Ocimum tenuiflorum as a potential antibacterial and nanocatalytic agent

Abstract: Biosynthesis of bimetallic Au-Ag core shell nanoparticle under ambient condition using Ocimum tenui orum (Krishna Tulsi) leaf extract is being reported for the rst time. For the biosynthesized bimetallic core shell nanoparticles (OTAuAgNPs) visual and spectrophotometric analysis was performed.Development of a deep purple color suggested the creation of OTAuAgNPs. It was then validated by UV-Vis spectrophotometry within 4 hours of incubation showing a surface plasmon resonance peak at 560 nm. FESEM-EDAX, FT-IR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…17 S. Nayak et al demonstrated 94.79% adsorption of the dye by using Au–Ag core shell nanoparticles. 18 ZnO is a widely used photocatalyst owing to its tunable band gap. Copper doping to the ZnO lattice can significantly reduce the band gap, as well as minimize the rate of charge recombination.…”
Section: Introductionmentioning
confidence: 99%
“…17 S. Nayak et al demonstrated 94.79% adsorption of the dye by using Au–Ag core shell nanoparticles. 18 ZnO is a widely used photocatalyst owing to its tunable band gap. Copper doping to the ZnO lattice can significantly reduce the band gap, as well as minimize the rate of charge recombination.…”
Section: Introductionmentioning
confidence: 99%